Greek and Latin Literature of the Roman Empire : From Augustus to Justinian. - Dihle, Albrecht (Taylor and Francis, 2013)
Professor Dihle sees the Greek and Latin literature between the 1st century B.C. and the 6th century A.D. as an organic progression. He builds on Schlegel's observation that art, customs and political life in classical antiquity are inextricably entwined and therefore should not be examined separately. Dihle does not simply consider narrowly defined `literature', but all works of cultural socio-historical significance, including Jewish and Christian literature, philosophy and science. Despite this, major authors like Seneca, Tacitus and Plotinus are considered individually. This work is an au.